A computational and experimental investigation of deep-blue light-emitting tetraaryl-benzobis[1, 2-d:4, 5-d′]oxazoles. Issue 9 (8th March 2022) - Wheeler, D.; Tannir, S.; Smith, E.; Tomlinson, A.; Jeffries-EL, M.
Abstract : In an effort to design deep-blue light emitting materials for use in OLEDs, the optical and electronic properties of a series of tetraarylbenzobis[1, 2- d :4, 5- d ′]oxazole (BBO) cruciforms were evaluated using density functional theory (DFT) and time-dependent DFT (TD-DFT). Abstract : In an effort to design deep-blue light emitting materials for use in OLEDs, the optical and electronic properties of a series of tetraarylbenzobis[1, 2- d :4, 5- d ′]oxazole (BBO) cruciforms were evaluated using density functional theory (DFT) and time-dependent DFT (TD-DFT). Of the nine possible combinations of phenyl-, furan-2-yl-, and thiophen-2-yl-substituted BBO cruciforms, five were predicted to have ideal optical and electronic properties for use in blue-light emitting diodes. These five cruciforms were synthesized and then characterized electrochemically and spectroscopically. Additionally, they were solution-processed into functional organic light-emitting diodes (OLED). Several of the OLEDs exhibited deep-blue EL ( λ EL < 452 nm; CIE y ≤ 0.12) with maximum luminance efficacies reaching 0.39 lm W −1 and maximum current efficiencies of 0.59 cd A −1 . A comparison of identical device architectures showed that heterocycles such as furan and thiophene helped improve device efficiencies with only a minor red-shift of the electroluminescence (EL). Although these BBO cruciforms produced the desired deep-blue emission their modest performance in host–guest OLEDs demonstrates the incorporation of heterocycles onto the BBO cruciform motif is detrimental to the fluroescence quantum yield. These results add to the knowledge base on structure–property relationships that will inform the design of better blue emitting materials.